Risk of cutaneous squamous cell carcinoma due to occupational exposure to solar ultraviolet radiation - Paulo, Marília Silva (2023)
Publisher Copyright: © 2023 Paulo et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.